1999
DOI: 10.1152/ajpheart.1999.276.2.h413
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion-based reentry: mechanism of initiation of ventricular tachycardia in isolated rabbit hearts

Abstract: The aim of the study was to determine whether facilitation of reentry by potassium-channel openers is related to dispersion of refractoriness and/or modification of anisotropic properties of ventricular myocardium. The dispersion of ventricular effective refractory period (VERP), longitudinal and transverse ventricular conduction velocities (θL and θT, respectively), and wavelength [λ = VERP × θ(L or T)] were studied in Langendorff-perfused left ventricular epicardium in 20 rabbits during infusion of increment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…These simulations suggest that Ca 2ϩ -dependent as well as drug-dependent modulation of Na ϩ channel inactivation could critically influence conduction during oxidative stress. Heterogeneities in the action potential duration, coupled with conduction velocity changes could lead to marked dispersion of repolarization and unidirectional conduction block, especially in the ischemic myocardium and border zone, a substrate that favors the development of re-entrant arrhythmias (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…These simulations suggest that Ca 2ϩ -dependent as well as drug-dependent modulation of Na ϩ channel inactivation could critically influence conduction during oxidative stress. Heterogeneities in the action potential duration, coupled with conduction velocity changes could lead to marked dispersion of repolarization and unidirectional conduction block, especially in the ischemic myocardium and border zone, a substrate that favors the development of re-entrant arrhythmias (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Searching for a noninvasive measurement of this substrate, body surface potential mapping proved successful 26 -29 but is impractical for wide clinical use. Measurement of QTd from the 12-lead surface ECG was proposed a decade ago 3 and was believed to provide a reasonably good reflection of the true myocardial heterogeneity of repolarization.…”
Section: Repolarization Heterogeneity: Noninvasive Assessment and Relmentioning
confidence: 99%
“…Although incompletely understood, one putative mechanism underlying this link is the development of spatial heterogeneity of myocardial action potential duration (APD) induced by a heightened sympathetic tone (15, 18,27,32). The resulting dispersion of ventricular repolarization facilitates reentrant VAs, which may degenerate into fibrillation and result in SCD (8,28).Prior studies have suggested that heterogeneous sympathetic innervation of the ventricles accounts for the spatial heterogeneities produced by sympathetic stimulation (18,22,23). Mantravadi et al (18) observed that sympathetic nerve stimulation reversed the sequence of ventricular repolarization, although this largely focused on the left ventricular free wall in an in vitro preparation.…”
mentioning
confidence: 99%
“…Although incompletely understood, one putative mechanism underlying this link is the development of spatial heterogeneity of myocardial action potential duration (APD) induced by a heightened sympathetic tone (15, 18,27,32). The resulting dispersion of ventricular repolarization facilitates reentrant VAs, which may degenerate into fibrillation and result in SCD (8,28).…”
mentioning
confidence: 99%